COMPARACIÓN DEL DESEMPEÑO COGNITIVO ENTRE GRUPOS DE NIÑOS CON TRASTORNOS DEL APRENDIZAJE Y SALUDABLES. - Parra Pinedo, Karely; Wong Izábal, Cristina Elizabeth; Sañudo Campos, Pedro Alexis (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología)
Learning disorders are characterized by difficulty in the acquisition of reading and mathematics, based on the alteration of cognitive processes that hinder their development. The objective of the study was to compare the cognitive functions in a group of children with learning disorders and healthy children. Fifty-eight children between 7 and 10 years of age participated, 36 of them with a diagnosis and the remaining 22 without a history of learning or behavioral problems, served as a control group. The tests of cognitive functions of the Infant Neuropsychological Assessment (ENI-2) were applied. In the results, a tendency is observed for the group with diagnoses to score below the control group in the language tests, the differences being significant in the reading of words (p = 0.000) and not words (p = 0.001). In conclusion, it is perceived that the clinical group presents deficiencies in the reading process, a process that was also strongly related to the deficit in executive functions, mainly in working memory and phonological awareness, for which the importance of the evaluation of other cognitive variables that may be directly associated with the different diagnoses.